Logbooks and Antarctic sealing. Approaching early- and late-19th-century exploitation strategies and their archaeological footprint - Salerno, Melisa Anabella (2023)
In the 19th century, sealing vessels visited the South Shetland Islands to exploit animal resources for the global skin and oil markets. The captains or mates of these vessels were responsible for keeping a logbook in which they recorded daily observations of weather conditions, hunting activities, etc. Despite the value of these documents as a source of information, archaeologists studying Antarctic sealing have not always relied on them. This paper examines the potential of logbooks for providing information that is relevant to the archaeological study of sealing in the South Shetland Islands. In particular, it discusses how documentary analysis of exploitation strategies can provide insight into the dynamics that influenced the configuration of sealers’ sites. To this end, we propose a methodology for investigating exploitation strategies, taking into account several archaeologically sensitive variables, including the number, location and duration of landings, as well as the activities carried out during these events. We have taken four logbooks dating from the early and late 19th century – specifically those of the Aurora (1820–1821), the Huron (1820–1822), the Thomas Hunt (1873–1874) and the Sarah W. Hunt (1887–1888) – as case studies to test the proposed methodology.